(untitled) (Philosophy and Progress, 2025)
A careful examination of global history reveals that numerous forms of discrimination have persisted from antiquity through to the modern era. As a direct consequence, countless castes, ethnic groups, minorities, and women have been systematically denied their rightful opportunities and entitlements. This deeply ingrained pattern of inequity extends into the professional sphere, where discriminatory practices remain prevalent. In the contemporary business landscape, job discrimination stands out as a core ethical challenge. In order to address this burning issue scholars have introduced different remedies. Such as back pay, equal opportunities, hiring, front pay, promotion, reasonable accommodation etc. Among the various remedies proposed, affirmative action has emerged as a significant and influential measure. This article delves into the nature of job discrimination, traces the historical genesis of affirmative action, and clarifies the legal framework governing such policies. It further examines the principal arguments both supporting and contesting affirmative action, shedding light on its farreaching social implications. In this paper, attempt has been made to show that this comprehensive analysis demonstrates how affirmative action helps cultivate a more equitable workplace environment and addresses the injustices that have shaped our shared past. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 1-29